Given the graph of the hyperbola:
![((y+2)^2)/(36)-((x+5)^2)/(64)=1](https://img.qammunity.org/2023/formulas/mathematics/high-school/zalj4nqzri5885x3rgjwpjeklzkdxcutiq.png)
The general equation of the given hyperbola is:
![((y-k)^2)/(a^2)-((x-h)^2)/(b^2)=1](https://img.qammunity.org/2023/formulas/mathematics/college/s1kgne2fewzyluu89sxmu2wqu6dp2foc21.png)
Where (h, k) is the center of the hyperbola
So, by comparing the equations:
Center = (h, k) = (-5, -2)
The hyperbola opens up and down
Since a =
![a=\sqrt[]{36}=6](https://img.qammunity.org/2023/formulas/mathematics/high-school/2v2impsqh46onhoo4hlhkqkljo8cja7vf5.png)
The coordinates of the vertices are: (h, k + a ) and (h, k - a)
h = -5, k = -2, a = 6
So, the coordinates are:
![(-5,-8),(-5,4)](https://img.qammunity.org/2023/formulas/mathematics/high-school/4q80ejddof8r3p9zt5vm3q306aznehqrmg.png)
The slopes of the asymptotes are:
![\pm(a)/(b)=\pm(6)/(8)=\pm(3)/(4)](https://img.qammunity.org/2023/formulas/mathematics/high-school/hz0uxtglg28tqm85yfhl19mxyj9bygxtk7.png)
The equation of the asymptotes are:
![\begin{gathered} y-k=\pm(a)/(b)(x-h) \\ y+2=\pm(3)/(4)(x+5) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/znjfsgxl10g4p8kut4df6qfhpb6h2leiib.png)